Pelatihan Pembuatan Kombucha Berbahan Lokal Kulit Batang Faloak sebagai Upaya Peningkatan Kesehatan dan Kewirausahaan - Paulus Risan F. Lalong; Maria Novalina Naben; Joanivita P. G. Soru; Aden Rimon Nome; Arkhangela G. Snoe (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The implementation of this Community Service (PkM) activity was motivated by the importance of maintaining health through the utilization of local herbal drinks, such as faloak stem bark. In addition to being a beverage rich in health benefits, this ingredient also has the potential to be developed into a high-value kombucha product and serve as a business unit. The empowerment of the Catholic Youth Community (OMK) of St. Gregory the Great Parish, Oeleta, Kupang City, East Nusa Tenggara, was the main focus of this activity, considering the importance of supporting the organization to become a productive and economically independent community. The primary objective of this PkM activity was to provide training on how to produce kombucha using local ingredients such as stem bark, so that it can be processed into a product that is both beneficial for health and has economic value. The implementation method of this activity was divided into three phases: preparation, implementation, and evaluation. The results of this activity showed an increase in participants' understanding, as indicated by higher post-test scores compared to pre-test scores. In addition, participants successfully produced kombucha made from faloak bark, which had undergone a 14-day fermentation process. Overall, this PkM activity received highly satisfactory responses from the participants, as reflected in the results of the evaluation questionnaire that was distributed.